Simultaneous implementation of the Bachelor, Masters and PhD degrees in nursing in the Universidad Jaume I. Castellón de la Plana, Spain - Loreto Maciá Soler; María Isabel Orts Cortés; María Eugenia Galiana Sánchez; Asunción Ors Montenegro (Investigación y Educación en Enfermería, 2013)
We present an experience in Nursing Education, accredited and implemented under the Spanish University System Reform in a Public University (Jaume I, Castellón) which had no previous nursing studies. The academics offered included all three educational levels (Bachelor, Master's and Doctorate), with an integrated theoretical-practical-clinical teaching methodology for the Bachelor Degree, competence acquisition in research in the Master's degree, and a doctorate formed by lines of research in the field of Nursing. Studies are accredited by the National Agency for Quality Assessment, which were authorized by the Spanish Ministry of Education and implanted between 2009 and 2011.